Fabrication and characterization of a multichannel 3D thermopile for chip calorimeter applications - Huynh, Tho Phuoc (2015)
Thermal sensors based on thermopiles are some of the most robust and popular temperature sensing technologies across industries and research disciplines. A chip calorimeter with a 3D thermopile layout with a large sensing area and multichannel capacity has been developed, which is highly desired for many applications requiring large reaction chambers or high throughputs, such as biofilm research, drug screening, etc. The performance of the device, including temperature sensitivity and heat power sensitivity, was evaluated. The capability to split the chip calorimeter to multiple channels was also demonstrated, which makes the chip calorimeter very flexible and powerful in many applications.